Kajian Upaya Peningkatan Pelayanan Angkutan Kota Di Balikpapan Propinsi Kalimantan Timur - Noviyanti, Noviyanti (Warta Penelitian Perhubungan, 2010)
CihJ of Balikpapan in zst Kalimantan Province is a cihJ of industn;, trade, EerUices and tourism, hasa ven; strategic position and has great economic potential both locally, regionally, nationally andinternationally. With the development of East Kalimantan Balikpapan particularly influential onvarious aspects including the transportation sector. To develop and realize the transportation StJStemnecessan; to determine appropriate policies and planning, so that the implementation of developmentcan be implemented with efficient transportation. To establish poliaj and good planningslwuld be supported btJ a number of data and information such as travel demand patterns andbottom-up approach, so that wisdom really made in accordance with local needs.Data were analyzed using Qualitative Descriptive Analysis Method is reviewing the condition ofurban transportation management and characteristics of the study area, too many overlapping routepermit, the existence of terminals and facilities that are not in accordance with the regulations, transportationplanning is not in accordance with the forecast demand and needs. whereas the expectedresults of the study are compiled in urban transportation planning effective and efficienJ in the studiedregion and as inputs for the improvement of urban transportation planning in order to improve transportation services.